Application of Videotape and Audiotape Self-Confrontation Procedures to Training Clinicians in Speech and Hearing Therapy. Final Report - Boone, Daniel R.; Prescott, Thomas E.; Denver Univ., CO. Speech and Hearing Center ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1971)
A study was conducted on the use of audiotape and videotape self-confrontation techniques in training speech and hearing therapy clinicians. The dissemination phase of the study consisted of a conference held in October, 1970 at the University of Denver entitled "Videotape and Audiotape Confrontation in Clinical Training." The findings and methodologies of the study were presented and a applied to various professional groups throughout the country. The application phase of the project involved training, cataloging, and utilizing all confrontation methodologies. The research phase determined that undergraduate grade point average appeared to be a good predictor of change resulting from each of three self-confrontation procedures: audio-confrontation, audio-video confrontation 10 category system, and audio-video confrontation 19 category system. (JY)
Sponsoring Agency: Bureau of Education for the Handicapped (DHEW/OE), Washington, DC.
Contract Number: OEG-0-70-4758(607).
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Audiotape Recordings; Grade Point Average; Hearing Therapy; Microcounseling; Predictor Variables; Speech Therapy; Therapists; Videotape Recordings